NURSING WORKER HEALTH: IDENTIFICATION OF SCIENTIFIC PRODUCTION - Vinicius Gomes Barros; Cristiane Helena Gallasch; Kátia Pontes Remijo; Karyme Lucila Jabra Lima; Patricia Campos Pavan Baptista; Vanda Elisa Andres Felli (Universidade Federal do Paraná, 2017)
The present study aimed to identify and analyze the scientific publications on health and nursing worker health generated by members of the Study Group on Occupational Health of Nursing and Health Personnel (GESTES). Descriptive-exploratory, documentary study of quantitative approach of data related to scientific publications of 1997 and 2016. In 20 years, 343 publications were generated. Analysis showed a predominance of publications by doctors (146; 42, 57%), followed by masters (105; 30, 61%) and graduate students (62; 18, 08%), most of them "abstracts and extended abstracts published in annals" (172; 50.15%), followed by articles published in scientific journals (74; 21, 57%). The theme "Exposure to workloads and/or work wear Process" prevailed, demonstrating the risks to worker health. It is concluded that the research group identified a significant volume of scientific publications on the referred theme during the study period.